MURTADHA MUTHAHHARI: PHILOSOPHY OF HISTORY (International Conference on Social and Islamic Studies, 2022)
This paper discusses Murtadha Motahhari's thoughts on historical philosophy and aims to reconstruct Murtadha Motahhari's thoughts regarding his historical philosophy from an Islamic perspective. The methods used are heuristics, source criticism, interpretation and historiography. The results of the study show that there are differences of opinion between the concept of western historical philosophy and Murtadha Mutahhari's philosophy of Islamic history. The concept of western philosophy of history holds that the philosophy of history from the point of view of the nature of history is material or material, from the point of view of the laws of history it has laws of determinism, and from the point of view of the movement of history or historical development it is determined by economic factors. Meanwhile, according to Murtadha Mutahhari, the philosophy of history in terms of the nature of history is not only material in nature but also intangible and supramaterial in nature. Human self.